2019
DOI: 10.5194/acp-19-10525-2019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the relative importance of northern African mineral dust sources using remote sensing

Abstract: Abstract. Northern African mineral dust provides the Amazon Basin with essential nutrients during the boreal winter months, when the trajectory of the Saharan dust plume is towards South America. This process, however, is still poorly understood. There is little knowledge of where the dust is coming from, and, thus, little information regarding the concentration of nutrients in the dust. This information is vital to assess the impact it will have on the Amazon. In order to further our understanding of the prob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…The detected FDs in our samples are thought to originate from African paleolakes (Bakker et al., 2019; Ben‐Ami et al., 2010; Prospero et al., 2002; Washington & Todd, 2005). Soil from paleolakes is comprised of diatomite, a mixture of low density FDs (0.8 g cm −3 ) and higher density authigenic minerals (2.7 g cm −3 ) (Bristow et al., 2010; Conrad & Lappartient, 1991).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The detected FDs in our samples are thought to originate from African paleolakes (Bakker et al., 2019; Ben‐Ami et al., 2010; Prospero et al., 2002; Washington & Todd, 2005). Soil from paleolakes is comprised of diatomite, a mixture of low density FDs (0.8 g cm −3 ) and higher density authigenic minerals (2.7 g cm −3 ) (Bristow et al., 2010; Conrad & Lappartient, 1991).…”
Section: Resultsmentioning
confidence: 61%
“…However, to our knowledge, our work is the first to show the transport of diatomite from African paleolakes to South America. Previous studies have suggested that multiple paleolakes within the Sahara including the Bodélé Depression and other paleolakes in the western Sahara are active dust sources that can transport mineral aerosols to South America (Bakker et al., 2019; Prospero et al., 2002). These paleolakes could explain the detection of FDs in our samples.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Formenti et al (2011) locate six major potential source areas (see their Figure 1): (1) northern Algeria and Tunisia, (2) southern Atlas and western Sahara‐Mauritania, (3) Mali‐Algerian border, (4) central Lybia, (5) Chad Bodele paleo lake, and (6) southern Egypt‐northern Sudan. It can be noted that most of these dust source regions correspond to alluvial deposit or paleolakes geomorphic regions (see Bakker et al, 2019; Damnati, 2000; and Figure 3 of Lézine et al, 2014). These areas are identified (red contours) on Figure 2 showing the good general match between IASI results and this compilation of independent results.…”
Section: Resultsmentioning
confidence: 99%
“…It can be noted that most of these dust source regions correspond to alluvial deposit or paleolakes geomorphic regions (see Bakker et al, 2019;Damnati, 2000;and Figure 3 of Lézine et al, 2014). These areas are identified (red contours) on Figure 2 showing the good general match between IASI results and this compilation of independent results.…”
Section: Iasi Dei Maps Over Saharamentioning
confidence: 99%
“…It can be noted that most such dust source regions correspond to alluvial deposit or paleolakes geomorphic regions (see, in particular, Fig. 3 of Bakker et al, 2019). These areas are identified (red contours) on Fig.…”
Section: Iasi Dust Aod Diurnal Cycle In the Regions Of Adrar And Bodelementioning
confidence: 90%